Wave filtering and firing modes in a light-sensitive neural circuit - Zhang, Xiu-fang; Ma, Jun (Journal of Zhejiang University. A. Science, 2021)
Inspired by the photoelectric effect, a phototube is incorporated into a simple neural circuit, and then the output voltage and dynamics become sensitive to external illumination within a specific frequency band. The firing modes are also dependent on the amplitude and frequency band in the illumination. In this paper, the signal outputs from a chaotic circuit are used as external optical signals, which are filtered and encoded by a phototube. Then, the functional neural circuit is excited to present a variety of firing modes and patterns. An exponential function of the filtering wave is proposed to discover the biophysical mechanism for frequency selection in the retina as most of wave bands of the external illumination are absorbed in the cathode material of the phototube while a specific band is effective in inducing a photocurrent for stimulating the visual neurons. Based on our light-sensitive neural circuit and model, external illumination is filtered and firing modes in the neuron are reproduced; furthermore, the mode transition induced by parameter shift is also investigated in detail. This result discovers the signal processing mechanism in the visual neurons and provides helpful guidance for designing artificial sensors for encoding optical signals and for repairing abnormalities in the retina of the visual system.